Analisis Sistem Dinamis pada Mesin Pengayak Pasir Tipe Vibrating Screen - Ruviana, Rizqa; Izzah, Anisah Nurul; Musyaroh; Fatkhurrohman; Faizin, Ahmad Khairul (Creative Research in Engineering (CERIE), 2025)
This research focuses on the modeling and dynamic system analysis of a sand sieving machine of the vibrating screen type. The primary objective is to enhance the effectiveness of the sand sieving process by comprehensively understanding the dynamic behavior of the machine under various operating conditions. The research methodology involves the development of a mathematical model to represent the system dynamics accurately and the implementation of numerical simulations using MATLAB software to analyze the machine’s performance under different parameters. Key findings reveal that critical parameters, such as vibration frequency and the mass of the sieve, have a significant impact on the machine’s operational efficiency and sieving quality. The results provide essential insights into the interplay between these parameters and the overall performance of the system.